Celebrity Endorsements On Social Media Towards Consumers Behavior / Alia Tasnim Mohd Anuar - Mohd Anuar, Alia Tasnim (2018)
Since the inception of social media, it has been widely adopted by users of various demographics around the globe. Celebrities are among those that have adopted social media as a means of communicating and interacting with their brands. These platforms also provide a way for celebrities to promote different products to their fans. A limited number of studies aimed to determine the factors that influence the effectiveness of celebrity endorsements on social media. Hence, the intent of this research is to study using a quantitative approach the effects of celebrity endorsements on social media on the fans of the celebrity endorsers and to identify some of the factors that are critical to a successful celebrity endorsement campaign on social media. This study employed the survey method through questionnaires adapted from Jatto (2014) to gather information from the participants. The questionnaire was designed and distributed by hand to the respondents. Data was analysed and exported directly to SPSS. Using descriptive statistics, the findings showed that respondents give positive view on the consumers’ perception where they find that celebrity endorsement on social media is good, sharing a great knowledge about the product and better than non-celebrity. Besides that, findings showed that credibility and attractiveness are important source characteristics for celebrity endorsements to be successful on social media. Next, the findings also showed that celebrity endorsement give an impact to the consumers’ brand awareness, their image of that brand and purchasing intention.